UPTAKE OF "˜FREE' MATERNITY SERVICES AMONG WOMEN IN RONGAI SUB- COUNTY HOSPITAL, NAKURU COUNTY - Kulei , Stella Jepkoech; Maranga, Alice kemunto (International Journal of Health, Medicine and Nursing Practice, 2020)
Purpose: Subsidized delivery services aim to reduce both maternal and neonatal' morbidities and mortalities. The uptake in Kenya is still low at about 51%. The objective of the study was to determine factors that influence utilization of subsidized delivery services. Methodology: A cross-sectional study was used. The study was done in Rongai Sub-County hospital, Nakuru County. The population consisted of women seeking maternity services at Rongai Sub-County Hospital. Results: About 60.8% of the respondents indicated they had knowledge while 39.2% of them indicated they did not have any knowledge on postnatal services. Conclusion: Majority of women already have knowledge on availability of free hospital care service. Women are more likely to seek services that are close to them, long distance to health facilities prevents them from seeking the services.